Neurological Manifestations of Hospitalized Patients with Covid-19: A Case Series Study - Zamanian M. H.; Janbakhsh A.; Mansouri F.; Sayad B.; Afsharian M.; Vaziri S.; Mahdavian B.; Afshar Z. M.; Miladi R.; Shirvani M.; Noori M.; Salimi M.; et al. (Acta Medica Bulgarica, 2021)
There are some reports about the neurological manifestations and complications of COVID-19. We present neurological manifestations in 6 hospitalized patients with COVID-19. The patients presented with common symptoms of COVID-19 along with common findings from high-resolution computed tomography (HRCT) scan such as ground-glass opacities (GGOs). Though, RT-PCR testing of SARS-CoV-2 was negative for all 6 cases. In the current report, acute cerebrovascular diseases affected older patients, while dementia, seizure and encephalopathy affected younger ones. Three of the 6 patients had proven strokes based on their neuroimaging. Four of the 6 patients had high d-dimer levels. Two of the cases experienced convulsion. The third patient presented with typical symptoms and signs of neuroleptic malignant syndrome. The sixth case was interesting for transient dementia. Unfortunately, four out of six patients died. The recent case series report the association between neurological involvements and COVID-19 infection. Clinicians should be alert of the neurologic symptoms in the setting of COVID-19, which might even be the first presentations of this infection.